Force of habit the mystical foundations of the narcotic - Howell, Simon Peter (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2012)
This thesis aims to investigate and deconstruct the relationship between the narcotic, its narrative, and western modernity. To reveal the relationship, this thesis argues that it is possible to understand the philosophical, political, cultural and ethical dimensions of western modernity through the ulterior lens of the narcotic. As such, this thesis investigates western modernity's relationship to (a) cocaine as a specific narcotic, and (b) the concept of the narcotic with all its attendant connotations of addictions, illegitimacy, transgression, illegality, and so on. Accordingly, the thesis is both interpretive of the historical narrative of the narcotic of cocaine, and generative in its deconstruction of the relationship between western modernity and the concept of the narcotic. The deconstruction of this relationship ultimately reveals both prior narratives not as oppositional, but as supplementary. This has radical consequences for the manner in which we engage with narcotic use and the user - if the narcotic is supplement to the logic of western modernity, at each attempt to expel the use and user of the narcotic, rather then create difference, we self implicate ourselves in that expulsion and distance. To seek a new and more just means of dealing with the concept of the narcotic, and its use, therefore requires a new epistemological framework which can at once contemplate both narratives at the same time. To this end, the thesis suggests the use of critical complexity theory as one such methodological tool, if supplemented by the thoughts and strategies of Derridian deconstruction and Foucauldian discourse analysis.
Keywords: Drug addiction -- Philosophy -- Research; Drug addiction -- Political aspects -- Research; Cocaine abuse -- Legal status, laws, etc. -- Research